Sistem Informasi Inventory Barang Berbasis Web Pada Apotek Afifah Farma Dengan Metode Waterfall - Sufajar Butsianto; Syahlan Sugiarto (Jurnal SIGMA, 2022)
The information systems are systems that process and provide information for decision-making in an organization. Inventory information system is a system used to process and provide information about inventory data in a company for decision making. Goods Inventory Information System at Apotek Afifah Farma still uses a manual process. The purpose of this research is to develop an ongoing inventory information system at Apotek Afifah Farma to support warehouse-based inventory of warehouse stock. The methodology used to develop the inventory information system of this item is the waterfall method and uses the PHP and MySQL programming languages. Data collection is done by means of observation and interviews. Inventory information systems can overcome problems related to the quality of information and the clarity of information produced. Admin as user of inventory information system concludes that this system can facilitate the processing, searching, and reporting of data in and out of warehouse goods. Keyword : Information Systems, Inventory, PHP, MYSQL